Electrode Kinetics of Vanadium Flow Batteries: Contrasting Responses of VII-VIII and VIV-VV to Electrochemical Pretreatment of Carbon. Issue 1 (23rd October 2015) - Bourke, A.; Miller, M. A.; Lynch, R. P.; Gao, X.; Landon, J.; Wainright, J. S.; Savinell, R. F.; Buckley, D. N.
Abstract : Electrochemical impedance spectroscopy and cyclic voltammetry were used to investigate the electrode kinetics of V II -V III and V IV -V V in H2 SO4 on glassy carbon, carbon paper, carbon xerogel, and carbon fibers. It was shown that, for all carbon materials investigated, the kinetics of V II -V III is enhanced by anodic, and inhibited by cathodic, treatment of the electrode; in contrast, the kinetics of V IV -V V is inhibited by anodic, and enhanced by cathodic, treatment. The potential region for each of these effects varied only slightly with carbon material. Rate constants were always greater for V IV -V V than for V II -V III except when anodized electrodes were compared, which may explain discrepancies in the literature. The observed effects are attributed to oxygen-containing functional-groups on the electrode surface. The considerable differences between the potentials at which enhancement of V II -V III and inhibition of V IV -V V occur indicates that they do not correspond to a common oxidized state of the electrode. Likewise inhibition of V II -V III and enhancement of V IV -V V do not correspond to a common reduced state of the electrode. It is possible that enhancement of both V II -V III and V IV -V V is due to the same (active) state of the electrode.